Comparison of various histochemical staining methods for identification of helicobacter pylori - Kanimozhi Gowsik; Archana V. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Helicobacter pylori infection plays a key role in the development of gastritis, Gastric ulcer and Gastric malignancy. More than half the world’s population is infected with this organism. The infection is more common in developing countries due to poor sanitation, overcrowding and low economic status. In view of this pathogenetic importance, diagnosis of H. Pylori is very important to institute eradication treatment. Various techniques are available for the detection of H. Pylori including serology, rapid urease test,13C-breath test, antigen detection in stool, histological examination and IHC.Aim: This study was conducted to compare various histochemical staining methods for identification of helicobacter pylori in endoscopic biopsy taken for gastritis. Materials andMethods: A total of 68 cases were included in this study over a period of six months. Slides were stained with 5 different histochemical stains. Sensitivity, Specificity and positive predictive value was calculated. As per literature modified giemsa was considered as standard and the findings from other stains were compared with it.Results: Out of 68 cases of gastric biopsy diagnosed of gastritis, 23 cases were positive for H. Pylori with Modified Giemsa, 17 with H&E, 23 with Toluidine blue, 21 with Acridine orange, 14 with Alcian blue.Conclusion: Histopathological examination is the gold standard method for identification. whichever stains used careful examination for the organism is essential. All the staining methods were easy to perform and cheap. Modified Giemsa, H&E and Acridine orange are more reliable.